Resin composition, cured product of resin composition, semiconductor device, and electronic component

By using free radically polymerizable curable resins, organic peroxides and sublimative polymerization inhibitors in the resin composition, the problem of curing at lower temperatures and prolonging the application period is solved, and stable bonding is achieved for high-function communication terminals and IoT applications.

CN119790112APending Publication Date: 2025-04-08NAMICS CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380062488.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-02
Filing Date
2023-07-28
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to cure the resin composition at lower temperatures while maintaining a long service life, especially in high-function communication terminals and IoT applications where there is a risk of damage to the components when bonding at high temperatures.

Method used

A resin composition containing a curable resin having a radical polymerizable property, an organic peroxide, and a sublimative polymerization inhibitor is used. Through the combination of these components, it can cure quickly at lower temperatures (such as below 80°C) and extend the applicable period.

Benefits of technology

The resin composition cured at lower temperatures is achieved, which extends the application period and ensures stable bonding of components under low temperature conditions, and is suitable for high-function communication terminals and IoT applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005288851910000201
    Figure BDA0005288851910000201
  • Figure BDA0005288851910000211
    Figure BDA0005288851910000211
  • Figure HDA0005288851920000011
    Figure HDA0005288851920000011
Patent Text Reader

Abstract

Provided are a resin composition which can be cured at a relatively low temperature and has a long pot life, a cured product, and a semiconductor device and an electronic component including the cured product. Provided are: a resin composition containing (A) a radically polymerizable curable resin, (B) an organic peroxide, and (C) a sublimable polymerization inhibitor; a resin composition additionally containing (D) conductive particles if necessary; a cured product obtained by curing the resin composition; and a semiconductor device and an electronic component containing the cured product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, a cured product of the resin composition, a semiconductor device and an electronic component. Background Art

[0002] With the popularization of high-function communication terminals such as smartphones and tablets, the demand for lightweight, miniaturized, and thinner products is increasing. In addition, the market for IoT (Internet of Things), where all objects are connected to the Internet, is growing rapidly. Various devices are being developed as IoT applications, including smartphones, but the inability to manufacture at high temperatures has become a problem due to problems with components. For example, the joining of components using solder needs to be done at a high temperature of more than 180°C, which damages the components, so a joining material that can be joined by curing at a low temperature is required.

[0003] For example, Patent Document 1 discloses a conductive resin composition as a conductive adhesive composition that can be cured at a temperature of about 150° C. and that can obtain a cured product having low elasticity after curing. The conductive resin composition comprises: (a) polyethylene glycol di(meth)acrylate, (b) a free radical generator, (c) a conductive filler, and (d) at least one selected from the group consisting of linear alkyl glycol di(meth)acrylate, polyester (meth)acrylate, and terminal-modified polybutadiene rubber.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-117860 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] Resin compositions capable of bonding members are required to be able to cure at relatively low temperatures and to have a long pot life and a long use time.

[0009] Therefore, an object of the present invention is to provide a resin composition, a cured product, a semiconductor device, and an electronic component that can be cured at a relatively low temperature, for example, 150° C. or lower and have a relatively long pot life.

[0010] Solutions for solving problems

[0011] Means for solving the above-mentioned problems are as follows, and the present invention includes the following aspects.

[0012] [1] A resin composition, characterized in that it comprises:

[0013] (A) a radically polymerizable curable resin,

[0014] (B) organic peroxides, and

[0015] (C) A sublimable polymerization inhibitor.

[0016] [2] The resin composition according to [1] above, further comprising (D) conductive particles.

[0017] [3] The resin composition according to [1] or [2], wherein the organic peroxide (B) comprises at least one selected from the group consisting of dialkyl peroxides, peroxyesters, peroxymonocarbonates, diacyl peroxides, peroxydicarbonates and peroxyketals.

[0018] [4] The resin composition according to any one of [1] to [3], wherein the 10-hour half-life temperature of the organic peroxide (B) is 70° C. or lower.

[0019] [5] The resin composition according to any one of [1] to [4], wherein the (A) radically polymerizable curable resin contains a compound having a (meth)acryloyl group.

[0020] [6] The resin composition according to any one of [1] to [5], wherein the (A) radically polymerizable curable resin comprises a bismaleimide compound.

[0021] [7] The resin composition according to any one of [1] to [6], wherein the (C) sublimable polymerization inhibitor comprises p-benzoquinone.

[0022] [8] A cured product obtained by curing the resin composition according to any one of [1] to [7].

[0023] [9] A cured product, wherein the room temperature elastic modulus of the cured product obtained by curing the resin composition according to any one of [1] to [7] at 80°C for 60 minutes is within a range of 0.005 GPa to 7.0 GPa.

[0024]

[10] A semiconductor device comprising the cured product according to [9] above.

[0025]

[11] An electronic component comprising the cured product according to [9] above.

[0026] Effects of the Invention

[0027] According to the present invention, there are provided a resin composition that can be cured at a relatively low temperature and has a relatively long pot life, a cured product obtained by curing the resin composition, a semiconductor device including the cured product, and an electronic component including the cured product. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The gas chromatograph shows the mass spectrum of benzoquinone at room temperature (about 25°C) and the mass spectrum of benzoquinone after heat treatment at 80°C for 2 minutes, 3 minutes, and 5 minutes, respectively, measured by gas chromatography-mass spectrometry (GC-MS). DETAILED DESCRIPTION

[0029] Hereinafter, the resin composition of the present disclosure, the cured product formed by curing the resin composition, the semiconductor device including the cured product, and the electronic component including the cured product will be described based on the embodiments. However, the embodiments shown below are examples for concretizing the technical idea of ​​the present invention, and the present invention is not limited to the following resin composition, the cured product formed by curing the resin composition, the semiconductor device including the cured product, and the electronic component including the cured product.

[0030] Resin composition

[0031] The resin composition of the first embodiment of the present invention comprises: (A) a radical polymerizable curable resin (hereinafter also referred to as "component (A)"), (B) an organic peroxide (hereinafter also referred to as "component (B)"), and (C) a sublimable polymerization inhibitor (hereinafter also referred to as "component (C)"). The resin composition of the second embodiment of the present invention preferably further comprises (D) conductive particles (hereinafter also referred to as "component (D)").

[0032] Resin compositions used in IoT applications such as smartphones, such as adhesives used in camera modules, are required to be able to cure at low temperatures below 80°C. In addition, the resin composition is required to have a long use time and a longer usable time as a pot life. Resin compositions that can be cured at low temperatures also use free radical polymerizable curable resins such as acrylates and methacrylates, and sometimes use a large amount of free radical initiators to enable curing at low temperatures. If a large amount of free radical initiators is used to enable curing at low temperatures below 80°C, there is a possibility that the curing reaction will proceed at an unexpected temperature, and the usable time as a pot life will be shortened.

[0033] The resin composition of the first embodiment of the present invention uses (A) a highly reactive free radical polymerizable curable resin and (B) an organic peroxide that can be used as an initiator for free radical polymerization reaction, and uses (C) a sublimable polymerization inhibitor to prevent undesired free radical polymerization reaction, thereby providing a resin composition that cures at a low temperature of, for example, 80° C. or less and has a long pot life.

[0034] The resin composition may further contain (D) conductive particles in addition to the components (A), (B) and (C). By containing the component (D), the resin composition can be used as a conductive adhesive for, for example, a camera module of a smartphone.

[0035] (A) The free radical polymerizable curable resin imparts curability and adhesion to the resin composition. Since the polymerization rate of the free radical polymerizable curable resin is relatively fast, it can be cured quickly. The free radical polymerizable curable resin composition is not particularly limited as long as it has free radical polymerizability. The free radical polymerizable curable resin preferably contains at least one selected from the group consisting of a compound having a (meth)acryloyl group, a bismaleimide compound and a carbamate (meth)acrylate compound, and may also contain two or more. (A) The free radical polymerizable curable resin preferably contains a compound having a (meth)acryloyl group. (A) The free radical polymerizable curable resin preferably contains a bismaleimide compound. For (A) the free radical polymerizable curable resin, for example, a compound having a (meth)acryloyl group alone can be used, a compound having a (meth)acryloyl group and a bismaleimide compound can be used, or a compound having a (meth)acryloyl group and a bismaleimide compound can be used. The three compounds having a (meth)acryloyl group, a bismaleimide compound and a carbamate (meth)acrylate compound can also be used in combination. When the heat resistance, moisture resistance and other stability and flexibility of the cured product formed by curing the resin composition are required, the resin composition preferably includes a compound with a (meth) acryloyl group and a bismaleimide compound. Sometimes, appropriate elasticity is also required for the cured product formed by the resin composition. When appropriate elasticity is required for the cured product, the resin composition preferably includes a carbamate (meth) acrylate compound. In this specification, "(meth) acryloyl" includes both methacryloyl and acryloyl. In addition, in this specification, "(meth) acrylate" includes both methacrylate and acrylate.

[0036] Component (A) preferably uses a liquid compound. If the compound used for component (A) is liquid, no solvent is required, and the generation of voids that are easily generated by solvent volatilization when the resin composition is cured can be suppressed. If there are voids in the cured product, it sometimes leads to a reduction in bonding strength and the generation of cracks. If it can be dispersed in the resin composition in a manner that suppresses the generation of voids, a solid compound can be used.

[0037] Relative to the total amount of 100 parts by mass of the resin composition, it is preferred that (A) contains a radically polymerizable curable resin in a range of 4 parts by mass or more and 90 parts by mass or less, more preferably in a range of 5 parts by mass or more and 50 parts by mass or less, and further preferably in a range of 7 parts by mass or more and 30 parts by mass or less. If the content of component (A) in the resin composition is in a range of 4 parts by mass or more and 90 parts by mass or less, a cured product that can be cured at a relatively low temperature and has good workability and low electrical resistance can be obtained. Furthermore, the amount of the radically polymerizable curable resin (A) is preferably in the range of 75 parts by mass or more and 99 parts by mass or less, more preferably in the range of 80 parts by mass or more and 98 parts by mass or less, further preferably in the range of 85 parts by mass or more and 97 parts by mass or less, and particularly preferably in the range of 90 parts by mass or more and 97 parts by mass or less, relative to 100 parts by mass of the total amount of all organic substances contained in the resin composition.

[0038] The compound having a (meth)acryloyl group may be any compound having a (meth)acryloyl group in the molecule, and may be an alkyl (meth)acrylate having a branched alkyl group such as isobutyl (meth)acrylate and tert-butyl (meth)acrylate; an ester of (meth)acrylic acid and an alicyclic alcohol such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentyl (meth)acrylate; an ester of (meth)acrylic acid and an aromatic alcohol such as phenoxyethyl acrylate; or an acrylamide compound such as hydroxyethyl acrylamide. The compound having a (meth)acryloyl group is preferably a monofunctional (meth)acrylate monomer such as phenoxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, and isobornyl (meth)acrylate, or a monofunctional acrylamide monomer such as hydroxyethyl acrylamide. A monofunctional (meth)acrylate monomer is particularly preferred, and from the viewpoint of imparting flexibility to the cured product, a (meth)acrylate monomer having a glass transition temperature (Tg) of 15° C. or less is more preferably included. On the other hand, if only a (meth)acrylate monomer having a glass transition temperature (Tg) of 15°C or less is contained, the curing hindrance caused by oxygen on the surface of the cured product becomes obvious, and unnecessary stickiness (stickiness) may be generated. In this case, it is further preferred to also combine a (meth)acrylate monomer having a glass transition temperature (Tg) of 15°C or more. If a (meth)acrylate monomer having a glass transition temperature (Tg) of 15°C or more is contained, the stickiness caused by the curing hindrance caused by oxygen on the surface of the cured product can be reduced. The glass transition temperature (Tg) of the (meth)acrylate monomer can be measured in the form of the glass transition temperature (Tg) when a homopolymer is made using a dynamic viscoelasticity measurement (DMA) or a thermomechanical analysis device (TMA). It should be noted that as a (meth)acrylate monomer, one or a mixture of two or more can be used. Specifically, the resin composition includes monofunctional (meth)acrylate monomers such as phenoxyethyl (meth)acrylate and dicyclopentyl (meth)acrylate. As described above, when the cured product requires moderate elasticity, the room temperature elastic modulus of the cured product can be easily adjusted, and the operability is improved. In the case of a multifunctional (meth)acrylate monomer having more than two (meth)acryloyl groups in one molecule, it is preferred that a straight-chain alkylene skeleton with a carbon number of 4 or more or a straight-chain oxyalkylene skeleton with a carbon number of 4 or more between adjacent (meth)acryloyl groups. If the multifunctional free radical polymerizable monomer has more than two (meth)acryloyl groups in one molecule, and a straight-chain alkylene skeleton with a carbon number of 4 or more or a straight-chain oxyalkylene skeleton with a carbon number of 4 or more between adjacent (meth)acryloyl groups, a cured product with a low elastic modulus and a large elongation and moderate flexibility after curing can be obtained. The straight-chain carbon number of the alkylene or oxyalkylene between adjacent (meth)acryloyl groups can be 4 or more, and may also have a branched chain.

[0039] Among the compounds having a (meth)acryloyl group, specific examples of acrylate monomers include Light Acrylate PO-A (phenoxyethyl acrylate, manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate IB-XA (isobornyl acrylate, manufactured by Kyoeisha Chemical Co., Ltd.), and FA-513AS (dicyclopentyl acrylate, manufactured by Showa Denko Materials Co., Ltd.). Specifically, examples of acrylamide monomers include HEAA (hydroxyethyl acrylamide, manufactured by KJ Chemicals Corporation).

[0040] When component (A) contains a (meth)acrylate monomer or an acrylamide monomer as a compound having a (meth)acryloyl group, relative to 100 parts by mass of the radical polymerizable curable resin (A), it is preferred that the compound having a (meth)acryloyl group is contained in a range of 3 parts by mass or more and 100 parts by mass or less, more preferably in a range of 5 parts by mass or more and 75 parts by mass or less, and further preferably in a range of 8 parts by mass or more and 60 parts by mass or less. If the content of the compound having a (meth)acryloyl group in component (A) in the resin composition is 3 parts by mass or more, the viscosity of the resin composition becomes lower, the handling property is good, and the operability is improved. As the content of the compound having a (meth)acryloyl group in component (A) in the resin composition decreases, the crosslinking density does not become too large, and the room temperature elastic modulus of the cured product becomes lower, so a cured product with moderate elasticity can be obtained.

[0041] Bismaleimide compounds can be used as long as they have a chemical structure sandwiched between two maleimide groups. By including bismaleimide compounds in the resin composition, a cured product having excellent stability such as heat resistance and moisture resistance can be obtained that can maintain flexibility and the cured product. The weight average molecular weight of the bismaleimide compound is preferably within the range of more than 500 and less than 7,000, more preferably within the range of more than 750 and less than 5,500, and further preferably within the range of more than 1,000 and less than 3,000. The bismaleimide compound can be a dimer acid-modified bismaleimide compound. Since the dimer acid-modified bismaleimide compound has reactive maleimide groups only at both ends, and there is no crosslinking reactive group in the molecular chain sandwiched between the two maleimide groups, the room temperature elastic modulus of the cured product formed by curing the resin composition can be suppressed to a lower level, and a cured product with moderate elasticity can be obtained. Compared to the ester compound with (meth) acryloyloxy in the compound with (meth) acryloyl group, the dimer acid modified bismaleimide compound has high hydrolysis resistance. In addition, since the dimer acid modified bismaleimide compound has a large alkyl chain in the molecule, it is highly hydrophobic. Therefore, the water resistance and moisture resistance of the resin composition comprising the dimer acid modified bismaleimide compound are high. In this specification, the weight average molecular weight is the value obtained by using a standard curve based on standard polystyrene using gel permeation chromatography (GPC).

[0042] Specifically, the bismaleimide compound is a dimer acid-modified bismaleimide compound, and liquid BMI-1500, liquid BMI-1700, and solid BMI-3000 (all manufactured by Designer Molecules) can be used. The bismaleimide compound can be used alone or in combination of two or more bismaleimide compounds having different chemical structures.

[0043] When component (A) includes bismaleimide compound, relative to (A) free radical polymerizable curable resin 100 mass parts, preferably include bismaleimide compound in the scope of more than 5 mass parts and below 40 mass parts, more preferably include bismaleimide compound in the scope of more than 15 mass parts and below 35 mass parts.If the content of the bismaleimide compound in the component (A) in resin combination is more than 5 mass parts, then the strength of the cured product formed by curing resin combination is reduced and there is the situation that the cured product with desired strength cannot be obtained.If the content of the bismaleimide compound in the component (A) of resin combination is below 40 mass parts, then the normal temperature elastic modulus of low cured product can be maintained, the cured product with appropriate elasticity can be obtained.

[0044] The carbamate (meth) acrylate compound preferably includes a carbamate (meth) acrylate oligomer having a weight average molecular weight of 1,000 or more and less than 20,000. By including the carbamate (meth) acrylate oligomer in the resin composition, the operability and reactivity of the resin composition will not be impaired, the room temperature elastic modulus of the cured product formed by curing the resin composition can be suppressed to a lower level, and a cured product with moderate elasticity can be obtained. The weight average molecular weight of the carbamate (meth) acrylate oligomer is preferably 1,000 or more and less than 20,000, more preferably 1,200 or more and 18,000 or less, and further preferably 1,500 or more and 15,000 or less. The carbamate (meth) acrylate oligomer can be used alone with one having the same weight average molecular weight, or two or more carbamate (meth) acrylate oligomers having different weight average molecular weights can be used as a mixture. When the resin composition contains a urethane (meth) acrylate oligomer having a weight average molecular weight of 20,000 or more, the viscosity of the resin composition increases, the workability decreases, and the reactivity of the resin composition decreases due to steric hindrance. Therefore, it is preferred that the resin composition does not substantially contain a urethane (meth) acrylate oligomer having a weight average molecular weight of 20,000 or more. In this specification, "substantially not containing" means that the object is not intentionally contained in the resin composition, and specifically means that the content of the object in the resin composition is 0 to less than 0.1% by mass.

[0045] As for the urethane (meth)acrylate oligomer, specifically, "UN-3320HA" with a weight average molecular weight of 1,500, "MBA-2CZ" with a weight average molecular weight of 1,600, "UN-333" with a weight average molecular weight of 3,000, "UN-6200" with a weight average molecular weight of 6,500, "UN-6304" with a weight average molecular weight of 13,000 (all manufactured by Negami Industries Co., Ltd.), "UV-3200B" with a weight average molecular weight of 10,000, and "UV-3000B" with a weight average molecular weight of 18,000 (all manufactured by Mitsubishi Chemical Group Corporation.) can be used.

[0046] When component (A) includes carbamate (meth) acrylate oligomer as carbamate (meth) acrylate compound, relative to 100 parts by mass of (A) free radical polymerizable curable resin, preferably, carbamate (meth) acrylate compound is included in the range of 5 parts by mass or more and 75 parts by mass or less, more preferably, carbamate (meth) acrylate compound is included in the range of 6 parts by mass or more and 50 parts by mass or less, and further preferably, carbamate (meth) acrylate compound is included in the range of 7 parts by mass or more and 30 parts by mass or less. If the content of carbamate (meth) acrylate compound in component (A) in the resin composition is more than 5 parts by mass, the room temperature elastic modulus of the cured product obtained by curing the resin composition can be reduced, and a cured product with moderate elasticity can be obtained. In addition, if the content of carbamate (meth) acrylate compound in component (A) of the resin composition is less than 75 parts by mass, it can be cured at a relatively low temperature, and the operability is good.

[0047] (B) The organic peroxide decomposes at a predetermined temperature to generate active species free radicals, and the free radical polymerization reaction of the radical polymerizable curable resin (A) is initiated by the active species free radicals. (B) The organic peroxide is a free radical polymerization initiator. (B) The organic peroxide preferably has a 10-hour half-life temperature of 70°C or less. As long as (B) The organic peroxide has a 10-hour half-life temperature of 70°C or less, the resin composition can be cured at a relatively low temperature. For example, when the resin composition is used in electronic components, the electronic components can be mounted on flexible wiring, etc. without causing damage to the electronic components due to heat. (B) The organic peroxide preferably has a 10-hour half-life temperature of 30°C or more and 70°C or less. If component (B) has a 10-hour half-life temperature of less than 30°C, the reactivity is too high, the stability of the resin composition is reduced, and there is a case where the desired pot life cannot be obtained. The 10-hour half-life temperature refers to the temperature when the time for the peroxide to decompose to its amount becoming one-half (1 / 2) is 10 hours.

[0048] In order to cure the resin composition at a relatively low temperature of, for example, 80° C. or less, the (B) organic peroxide preferably comprises at least one selected from the group consisting of dialkyl peroxides, peroxyesters, peroxymonocarbonates, diacyl peroxides, peroxydicarbonates, and peroxyketals. The organic peroxide more preferably comprises at least one selected from peroxydicarbonates or peroxyesters. The peroxyester is preferably a compound having a peroxyneodecanoate structure.

[0049] (B) Organic peroxides that can be used include, specifically, bis(4-tert-butylcyclohexyl)peroxydicarbonate (product name: PEROYL TCP, NOF Corporation, 10-hour half-life temperature: 40.8° C.), 1,1,3,3-tetramethylbutyl peroxyneodecanoate (product name: Luperox 810, ARKEMA Yoshitomi, Ltd., 10-hour half-life temperature: 44° C.), tert-amyl peroxyneodecanoate (product name: Luperox 546, ARKEMA Yoshitomi, Ltd., 10-hour half-life temperature: 46° C.), tert-butyl peroxyneodecanoate (product name: Luperox 10, ARKEMA Yoshitomi, Ltd., 10-hour half-life temperature: 48° C.), dicetyl peroxydicarbonate (product name: Perkadox 24L, KAYAKU NOURYON CORPORATION, 10-hour half-life temperature: 48°C), di-sec-butyl peroxydicarbonate (product name: Luperox225, ARKEMA Yoshitomi, Ltd., 10-hour half-life temperature: 51°C), 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate (product name: PEROCTA O, NOF Corporation, 10-hour half-life temperature: 65.3°C), dilauroyl peroxide (product name: PEROYL L, NOF Corporation, 10-hour half-life temperature: 61.6°C), etc.

[0050] In the resin composition, relative to 100 parts by mass of the radical polymerizable curable resin of component (A), component (B) is preferably included in the range of 0.1 parts by mass or more and 30 parts by mass or less, more preferably in the range of 1 parts by mass or more and 20 parts by mass or less, and further preferably in the range of 3 parts by mass or more and 10 parts by mass or less. When the content of component (B) in the resin composition is in the range of 0.1 parts by mass or more and 30 parts by mass or less, it can fully react even at a low temperature of, for example, 80°C or less. If the content of component (B) in the resin composition exceeds 30 parts by mass, unreacted component (B) may remain in the cured product, and there is a situation where the cured product is heated by the remaining component (B).

[0051] The inhibitor can inhibit free radical polymerization and extend the pot life. (B) The organic peroxide decomposes at a relatively low temperature to generate active free radicals, and initiates the free radical polymerization of the curable resin (A) with free radical polymerization. Even at room temperature (normal temperature), for example, about 25°C, the organic peroxide (B) will decompose, and there is a possibility of initiating an undesirable free radical polymerization reaction. By using an inhibitor, undesirable free radical polymerization reactions at room temperature (normal temperature) can be inhibited, thereby extending the pot life. In the present invention, by using (C) a sublimation inhibitor, the inhibitor sublimates at the temperature at which the free radical polymerization reaction is expected to be initiated and becomes non-existent, and a cured product can be obtained by the desired free radical polymerization reaction. In this specification, "sublimation" refers to the property of a substance changing from a solid to a gas (or from a gas to a solid), and refers to the property of changing from a solid to a gas and volatilizing during heat treatment. That is, since the "sublimation" inhibitor does not change phase to a liquid, it does not have a boiling point. For example, a polymerization inhibitor having the characteristic that the mass spectrum peak in GC-MS is reduced by 90% or more when heat-treated at 80°C for more than 2 minutes and less than 5 minutes is defined as a "sublimable polymerization inhibitor". (C) The sublimable polymerization inhibitor preferably sublimates at 80°C or less. (C) The sublimable polymerization inhibitor preferably has a sublimation temperature of 80°C or less. In order to suppress undesirable free radical polymerization reactions, the sublimation temperature is preferably 40°C or more and 80°C or less, and may also be 45°C or more and 80°C or less.

[0052] (C) The sublimable polymerization inhibitor preferably contains p-benzoquinone. The sublimability of p-benzoquinone can be confirmed as follows.

[0053] The mass spectra of p-benzoquinone at room temperature (about 25°C) and after heat treatment at 80°C for 2 minutes, 3 minutes, and 5 minutes were measured using a gas chromatograph-mass spectrometer (GC-MS) (e.g., GC-MSQP2010, manufactured by Shimadzu Corporation). Figure 1 The figure shows the mass spectrum of 10 mg of p-benzoquinone at room temperature (about 25°C) measured by GC-MS and the mass spectrum of p-benzoquinone after heat treatment at 80°C for 2 minutes, 3 minutes, and 5 minutes measured by GC-MA. Figure 1 As shown, in the mass spectrum of benzoquinone after heat treatment at 80°C for different time periods, since the specific peak existing in the mass spectrum of para-benzoquinone at room temperature (about 25°C) no longer exists, para-benzoquinone disappears due to sublimation during heat treatment at 80°C, which confirms its sublimability.

[0054] (C) As the sublimable polymerization inhibitor, specifically, p-benzoquinone (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) can be used as a polymerization inhibitor having sublimation properties at 80°C or lower.

[0055] In the resin composition, the component (C) is preferably contained in the range of 0.1 to 5.0 parts by mass, more preferably in the range of 0.2 to 4.0 parts by mass, and further preferably in the range of 0.3 to 3.0 parts by mass, relative to 100 parts by mass of the organic peroxide of the component (B). When the content of the component (C) in the resin composition is in the range of 0.1 to 5.0 parts by mass, relative to 100 parts by mass of the component (B), the cleavage of the organic peroxide at room temperature can be suppressed and the radical polymerization reaction can be suppressed, thereby extending the pot life.

[0056] When the resin composition further contains (D) conductive particles, the conductive particles are used to impart thermal conductivity and / or electrical conductivity to the resin composition. The resin composition containing the conductive particles of component (D) can also be used as a conductive adhesive for bonding electronic components, etc. The conductive particles of component (D) refer to particles having an average particle size of 0.01 μm or more and 100 μm or less and an electrical conductivity of 10 6 Particles with a particle size of S / m or more. The conductive particles of component (D) may be formed by forming a conductive material into particles, or may be formed by covering a core (core particle) with a conductive material. The core contained in the conductive particles may be formed of a non-conductive material as long as a portion of the core is covered with a conductive material. The conductive particles of component (D) include metal powder and coating powder. The average particle size of the conductive particles can be measured by a laser diffraction scattering method, and the average particle size refers to the particle size when the cumulative frequency is 50% in the volume-based particle size distribution (median particle size: D50).

[0057] The conductive material used in the (D) conductive particles is not particularly limited as long as it is a material that imparts thermal conductivity and / or electrical conductivity to the resin composition. Examples of the conductive material include gold, silver, nickel, copper, palladium, platinum, bismuth, tin and alloys thereof (particularly bismuth-tin alloys, solder, etc.), aluminum, indium tin oxide, silver-coated copper, silver-coated aluminum, metal-coated glass balls, silver-coated fibers, silver-coated resins, antimony-doped tin, tin oxide, carbon fibers, graphite, carbon black and mixtures thereof.

[0058] Regarding the (D) conductive particles, when considering thermal conductivity and electrical conductivity, the conductive material is preferably at least one metal selected from the group consisting of silver, nickel, copper, tin, aluminum, silver alloys, nickel alloys, copper alloys and aluminum alloys, more preferably at least one metal selected from the group consisting of silver, copper and nickel, further preferably silver or copper, and particularly preferably silver.

[0059] In one embodiment, the conductive particles (D) are preferably silver particles. In another embodiment, the conductive particles (D) are preferably copper particles. As described above, the silver particles or copper particles each include a coating powder in which at least a portion of the surface of the core particle is coated with silver or copper.

[0060] (D) As the conductive particles, specifically, silver powders such as "EA79613" and "K79121P" (both manufactured by Metalor Technologies Japan) can be used.

[0061] The resin composition may contain 95 parts by mass or less of the component (D), or 92 parts by mass or less of the component (D). In one embodiment, the conductive particles (D) are preferably contained in an amount of 10 parts by mass or more and 95 parts by mass or less, more preferably in an amount of 20 parts by mass or more and 95 parts by mass or less, and further preferably in an amount of 50 parts by mass or more and 95 parts by mass or less, and may be contained in an amount of 70 parts by mass or more and 95 parts by mass or less, relative to 100 parts by mass of the total amount of the resin composition.

[0062] (D) The shape of the conductive particles is not particularly limited, and may be any shape such as spherical, amorphous, flake (scaly), filament (needle) and dendrite. Flake refers to a shape having an aspect ratio of 2 or more represented by "major diameter / minor diameter", including flat plate shapes such as plate-like and scaly. For the major diameter and minor diameter of the particles constituting the conductive particles, the aspect ratio can be calculated based on the image obtained by a scanning electron microscope (SEM), from the average value of the major diameter and minor diameter of any 20 particles. "Major diameter" refers to the diameter with the longest distance among the line segments passing through the approximate center of gravity of the particles in the particle image obtained by SEM, and "minor diameter" refers to the diameter with the shortest distance among the line segments passing through the approximate center of gravity of the particles in the particle image obtained by SEM. (D) The conductive particles may include particles of different shapes.

[0063] (D) When the conductive particles are silver particles, the silver particles preferably have a tap density of 1.5 g / cm 3 More preferably, 2.0 g / cm 3 Above and 6.0g / cm 3 In the following range. If the tap density of the silver particles is too low, the silver particles cannot be dispersed in the resin composition at a higher density, and the conductivity of the obtained cured product is easily reduced. If the tap density of the silver particles is too high, the silver particles become easy to separate and precipitate in the resin composition, and there is a situation where the conductivity is reduced. The tap density can be measured according to JIS Z 2512 metal powder-tap density measurement method.

[0064] When the (D) conductive particles are silver particles, the average particle size (D50) is preferably in the range of 0.05 μm to 50 μm, more preferably in the range of 0.1 μm to 20 μm, and even more preferably in the range of 0.1 μm to 15 μm, from the viewpoint of imparting conductivity to the cured product and the viewpoint of handling properties taking into account the fluidity of the resin composition.

[0065] (D) When the conductive particles are silver particles, the specific surface area is preferably 4.0 m 2 / g or less, more preferably 0.1m 2 / g or more and 3.0m 2 / g or less. The specific surface area can be measured by the BET method. If the specific surface area of ​​the silver particles is too large, the viscosity of the resin composition increases and the handling property is reduced. If the specific surface area of ​​the silver particles is too small, the contact area between the silver particles decreases and the conductivity is reduced.

[0066] The resin composition may contain component (A), component (B) and component (C), and may further contain component (D). It may contain components other than component (A), component (B) and component (C), or may not contain components other than component (A), component (B), component (C) and component (D). The resin composition may consist of component (A), component (B) and component (C), or may consist of component (A), component (B), component (C) and component (D).

[0067] The resin composition may also contain at least one additive selected from the group consisting of inorganic pigments, organic pigments, silane coupling agents, leveling agents, thixotropic agents, insulating particles, coupling agents and other interface treatment agents, dyes, plasticizers, defoaming materials, defoaming agents and antioxidants, within the range that does not hinder the effects of the present invention or in order to improve the effects of the present invention.

[0068] Relative to 100% by mass of the resin composition, the content of the additive contained in the resin composition may be 10.0% by mass or less, 8.0% by mass or less, or 5.0% by mass or less. The content of the additive contained in the resin composition may be 0.10% by mass or more, 0.20% by mass or more, 0.30% by mass or more, or 0.50% by mass or more.

[0069] Method for producing resin composition

[0070] The resin composition can be manufactured by mixing component (A), component (B) and component (C), and then component (D) as required. The resin composition can also be manufactured by mixing each component with an additive as required. The manufacturing method of the resin composition is not particularly limited. The resin composition can be manufactured by mixing the raw materials of each component using a mixer such as a Henschel mixer, a roller mill, and a three-roll mill. The components of the resin composition can be mixed simultaneously, or a part can be pre-mixed and then the rest can be mixed. In addition, the aforementioned devices can also be appropriately used in combination to manufacture the resin composition.

[0071] The resin composition preferably has curability when cured at 80° C. for 60 minutes. The curability can be confirmed by visual inspection or touch as described in the evaluation method of curability described later.

[0072] The resin composition preferably has a pot life of more than 24 hours, more preferably has a pot life of more than 48 hours, and further preferably has a pot life of more than 72 hours. "Pot life" refers to the time after the resin composition is made to maintain the state in which the resin composition can be used. Using a Brookfield viscometer RVT type viscometer (rotor: SC4-14 rotor, measuring temperature 25 ° C), the viscosity of the resin composition just made and the viscosity of the resin composition after being placed at room temperature (about 25 ° C) for a specified time are measured at a rotation speed of 10 rpm. The viscosity of the resin composition just made is set to 1.0, and the change ratio of the viscosity of the resin composition placed for a specified time is calculated as the thickening rate, and the time when the thickening rate becomes more than 1.5 is expressed as the pot life time. When the value of the thickening rate is large, it means that the viscosity of the resin composition increases over time. In addition, when the thickening rate is small, it means that the change in viscosity over time is small. The pot life can be adjusted by the compounding amount of component (B) and component (C) in the resin composition.

[0073] Method for supplying resin composition

[0074] The resin composition can be supplied using a jet distributor, an air distributor, etc. In addition, the resin composition can be supplied using a known coating method (dip coating, spray coating, rod coater coating, gravure coating, reverse gravure coating, spin coater coating, etc.) and a known printing method (lithographic printing, carton printing, metal printing, offset printing, screen printing, gravure printing, flexographic printing, inkjet printing, etc.).

[0075] Curing conditions of resin composition

[0076] For example, the resin composition can be cured by heating at 40° C. to 120° C. The curing temperature of the resin composition is preferably 40° C. to 120° C., more preferably 50° C. to 100° C. The heating time for curing the resin composition is preferably 15 minutes to 4 hours, more preferably 30 minutes to 2 hours.

[0077] A cured product obtained by curing the resin composition

[0078] By curing the resin composition, a cured product formed by curing the resin composition can be obtained. The room temperature elastic modulus of the cured product formed by curing the resin composition at 80 ° C for 60 minutes is preferably within the range of more than 0.005GPa and less than 7.0GPa, more preferably within the range of more than 0.05GPa and less than 6.0GPa, and more preferably within the range of more than 0.1GPa and less than 5.0GPa. "Normal temperature elastic modulus" refers to the degree of flexibility at room temperature shown by the cured product of the resin composition. It can be said that the lower the room temperature elastic modulus, the higher the flexibility. The room temperature elastic modulus can be measured as shown in the measuring method in the embodiment described later, using a viscoelasticity measuring device (DMA) (such as DMA7100, Hitachi High-Tech Corporation. system) to determine the sample coating of the prescribed film thickness obtained by curing the resin composition. The room temperature elastic modulus of the cured product of the resin composition can be adjusted by the molecular weight and compounding amount of component (A).

[0079] Semiconductor devices

[0080] The resin composition can be suitably used for forming an interlayer insulating film, a protective layer, or a conductive adhesive of a semiconductor device. For example, when the resin composition is used as a conductive adhesive of a semiconductor device, the semiconductor device includes a cured product obtained by curing the resin composition.

[0081] Electronic components

[0082] The resin composition can be suitably used as a conductive adhesive for electronic components. For example, when the resin composition is used as a conductive adhesive for electronic components, the electronic components include a cured product obtained by curing the resin composition. Semiconductor devices including the resin composition and its cured product can be used, for example, for electronic components of electronic devices such as mobile phones, smart phones, notebook computers, tablet terminals, and camera modules.

[0083] Example

[0084] The present invention will be described in more detail below by way of examples. The present invention is not limited to these examples. In the following examples and comparative examples, the numbers indicating the blending ratios of the components contained in the resin composition represent parts by mass unless otherwise specified.

[0085] Component (A): Radically polymerizable curable resin

[0086] A-1: Light Acrylate PO-A (phenoxyethyl acrylate: manufactured by Kyoei Chemical Co., Ltd.)

[0087] A-2: FA-513AS (dicyclopentyl acrylate: Showa Denko Materials Co., Ltd.)

[0088] A-3: HEAA (Hydroxyethyl acrylamide: KJ Chemicals Corporation)

[0089] A-4: BMI-1500 (bismaleimide resin: manufactured by Designer Molecules)

[0090] A-5: UN-6200 (urethane acrylate oligomer, weight average molecular weight (Mw) 6,500: manufactured by Negami Industries, Ltd.)

[0091] A-6: MBA-2CZ (urethane acrylate oligomer, weight average molecular weight (Mw) 1,600: Negami Industries, Ltd.)

[0092] A-7: UV-3000B (urethane acrylate oligomer, weight average molecular weight (Mw) 18,000: manufactured by Mitsubishi Chemical Group Corporation)

[0093] A-8: UN-3320HA (urethane acrylate oligomer, weight average molecular weight (Mw) 1,500: manufactured by Negami Industries, Ltd.)

[0094] Ingredient (B): Organic peroxide

[0095] B-1: PEROYL TCP (peroxydicarbonate, 10-hour half-life temperature (T10) 40.8°C, manufactured by NOF Corporation)

[0096] B-2: Luperox 810 (1,1,3,3-tetrabutyl peroxydecanoate, 10-hour half-life temperature (T10) 44°C, manufactured by ARKEMA Yoshitomi, Ltd.)

[0097] B-3: Luperox 546 (tert-amyl peroxydecanoate, 10-hour half-life temperature (T10) 46°C, ARKEMA Yoshitomi, Ltd.)

[0098] B-4: Luperox 10 (tert-butyl peroxydecanoate, 10-hour half-life temperature (T10) 48°C: manufactured by ARKEMA Yoshitomi, Ltd.)

[0099] B-5: PEROCTAO (1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, 10-hour half-life temperature (T10) 65.3°C, manufactured by NOF Corporation)

[0100] Component (C): Sublimation inhibitor

[0101] C-1: p-Benzoquinone (p-Benzoquinone: FUJIFILM Wako Pure Chemical Industries, Ltd.) has sublimation properties when subjected to heat treatment at 80° C. for 2 minutes to 5 minutes.

[0102] Ingredient (C'): Inhibitor

[0103] C'-2: N-nitroso-N-phenylhydroxylamine aluminum: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0104] C'-3:HQ (Hydroquinone: Fujifilm Wako Pure Chemical Industries, Ltd.)

[0105] C'-4: TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl radical: Koei Chemical Industry Co., Ltd.)

[0106] Component (D): Conductive particles

[0107] D-1: EA79613 (silver powder, average particle size based on laser diffraction scattering method 7 μm, BET specific surface area 0.3 m 2 / g, tap density according to JIS Z2512: 5.1 g / cm 3 , Metalor Technologies Japan)

[0108] D-2: K 79121P (silver powder, average particle size based on laser diffraction scattering method 7 μm, BET specific surface area 2.3 m 2 / g, tap density according to JIS Z2512: 2.7g / cm 3 , Metalor Technologies Japan)

[0109] Examples 1 to 16, Comparative Examples 1 to 3

[0110] Component (A), component (B), component (C) or component (C'), and component (D) are mixed in a manner to form the mixing ratio shown in Table 1 or 2, and stirred and mixed using a three-roll mill to manufacture each resin composition of the embodiment and the comparative example. The numerical values ​​without units in the table represent "parts by mass". "Mw" in the table represents "weight average molecular weight". "T10" in the table represents "10-hour half-life temperature". In addition, the symbol "-" in the table indicates that the corresponding component is not included in the resin composition or cannot be measured.

[0111] The following evaluations were performed on each resin composition of the examples and comparative examples, and on a cured product obtained by curing each resin composition.

[0112] Curing at 80°C for 60 minutes

[0113] A 100 μm thick tape was placed on a glass slide as a gap, and each resin composition was applied on the slide to form a coating film, forming a test piece as a cured product obtained by curing the resin composition at 80°C for 60 minutes. Whether the test piece is cured is visually confirmed, and whether the components derived from the resin composition are attached to the fingers is confirmed by touch. The test piece that can be confirmed to be cured by visual inspection and touch is recorded as "G (good)", and the test piece that cannot be confirmed to be cured by visual inspection and touch is recorded as "B (poor)".

[0114] Applicable period

[0115] The viscosity of each resin composition of the examples and comparative examples just after production (within 3 hours after production) and the viscosity of each resin composition of the examples and comparative examples after production in a syringe (the resin composition is filled into the syringe immediately after production and made into a sealed state) are measured at a rotation speed of 10 rpm using a Brookfield viscometer RVT viscometer (rotor: SC4-14 rotor, measuring temperature 25°C). The viscosity change of the resin composition after standing at 25°C when the viscosity of the resin composition just after production is set to 1.0 is expressed as the thickening rate. The time until the thickening rate becomes 1.5 or more is taken as the pot life time and is recorded in Table 1 or 2. In the table, if the pot life time exceeds 72 hours, it is expressed as ">72".

[0116] Elastic modulus at room temperature

[0117] In such a way that the film thickness during curing becomes 200 ± 50 μm, each resin composition in the embodiment and the comparative example is coated on a slide glass attached with Teflon (registered trademark) tape to form a coating film, and the resin composition is cured for 60 minutes at 80°C in an air convection oven to obtain a cured product. After the coating-like cured product is peeled off from the slide glass attached with Teflon tape, a test piece of 40 mm × 5 mm in size is cut out using a cutter to obtain a test piece of the cured product. The cut of the cutter is processed to be smooth using sandpaper. The obtained test piece is measured according to the following conditions using a viscoelasticity measuring device (DMA) (DMA7100, Hitachi High-Tech Corporation.) according to JIS C6481.

[0118] Deformation Mode: Tension

[0119] Measurement mode: Ramp

[0120] Frequency: 10Hz

[0121] Strain amplitude: 5μm

[0122] Minimum tension / pressure: 50mN

[0123] Tension / compression force gain: 1.2 Force amplitude initial value: 50mN Movement waiting time: 8 seconds Creep waiting time coefficient: 0 Temperature: 25℃.

[0124] [Table 1]

[0125]

[0126] [Table 2]

[0127]

[0128] As shown in Tables 1 and 2, each resin composition of Examples 1 to 16 has good curing properties under heating at 80°C for 60 minutes, and has a long pot life of 72 hours or more. In addition, each cured product obtained by curing each resin composition of Examples 1 to 16 at 80°C for 60 minutes has a room temperature elastic modulus of 0.008 GPa or more and 5.0 GPa or less, and has excellent flexibility.

[0129] For the resin composition of Comparative Example 1, since the polymerization inhibitor is not sublimable, the resin composition is not completely cured under heating at 80°C for 60 minutes, and a part of it is not cured, and the curing property is not good. For the resin composition of Comparative Example 2, since the polymerization inhibitor is not sublimable, the applicable period is 12 hours, which is short, and the handling property is not good. For the resin composition of Comparative Example 3, since the polymerization inhibitor is not sublimable, although the applicable period is more than 72 hours, which is long, the resin composition is not completely cured under heating at 80°C for 60 minutes, and the curing property is not good. In addition, the resin composition of Comparative Example 3 cannot form a coating film because it is not cured, so the elastic modulus at room temperature cannot be measured.

[0130] Industrial Applicability

[0131] The resin composition of the present invention can be used in semiconductor devices. The resin composition of the embodiment of the present invention, the cured product obtained by curing the resin composition, and the semiconductor device including the cured product can be used as electronic components of electronic devices such as mobile phones, smart phones, notebook computers, tablet terminals, and camera modules.

Claims

1. A resin composition, characterized in that Include: (A) a radically polymerizable curable resin, (B) organic peroxides, and (C) A sublimable polymerization inhibitor. 2 . The resin composition according to claim 1 , further comprising (D) conductive particles.

3. The resin composition according to claim 1 or 2, wherein The (B) organic peroxide includes at least one selected from the group consisting of dialkyl peroxides, peroxyesters, peroxymonocarbonates, diacyl peroxides, peroxydicarbonates, and peroxyketals.

4. The resin composition according to any one of claims 1 to 3, wherein The 10-hour half-life temperature of the (B) organic peroxide is 70° C. or lower.

5. The resin composition according to any one of claims 1 to 4, wherein The (A) radically polymerizable curable resin includes a compound having a (meth)acryloyl group.

6. The resin composition according to any one of claims 1 to 5, wherein The (A) radically polymerizable curable resin includes a bismaleimide compound.

7. The resin composition according to any one of claims 1 to 6, wherein The (C) sublimable polymerization inhibitor includes p-benzoquinone. 8 . A cured product obtained by curing the resin composition according to claim 1 .

9. A solidified product, wherein The room-temperature elastic modulus of a cured product obtained by curing the resin composition according to any one of claims 1 to 7 at 80°C for 60 minutes is within a range of 0.005 GPa to 7.0 GPa. 10 . A semiconductor device comprising the cured product according to claim 9 .

11. An electronic component comprising the cured product according to claim 9.

Citation Information

Patent Citations

  • Conductive resin composition, conductive resin composition for dispensing, die attach agent, and semiconductor device

    JP2016117860A